2019
DOI: 10.1371/journal.pone.0215779
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of ATP7B in 102 south Indian families with Wilson disease

Abstract: Wilson disease (WD) is an autosomal recessive disorder, characterized by excessive deposition of copper in various parts of the body, mainly in the liver and brain. It is caused by mutations in ATP7B . We report here the genetic analysis of 102 WD families from a south Indian population. Thirty-six different ATP7B mutations, including 13 novel ones [p.Ala58fs*19, p.Lys74fs*9, p.Gln281*, p.Pro350fs*12, p.Ser481*, p.Leu735Arg, p.Val752Gly, p.Asn812fs*2, p.Val845Ala, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…In three patients a single heterozygous pathogenic variant was detected, leaving the possibility of variation in other genes or presence of modifiers, deep intronic variants, or intragenic deletions. As reported previously, the mutations were distributed across the gene in different exons including 2, 8, 13, 14, 15,17,18, and 19 [7][8][9][10] . Most mutations (~45%) were located in exons 2 and 8 (n=7) & were clustered at the ATP binding domain.…”
mentioning
confidence: 81%
“…In three patients a single heterozygous pathogenic variant was detected, leaving the possibility of variation in other genes or presence of modifiers, deep intronic variants, or intragenic deletions. As reported previously, the mutations were distributed across the gene in different exons including 2, 8, 13, 14, 15,17,18, and 19 [7][8][9][10] . Most mutations (~45%) were located in exons 2 and 8 (n=7) & were clustered at the ATP binding domain.…”
mentioning
confidence: 81%
“…More than 750 mutations in ATP7B gene have been reported to date. [ 19 ] After the first report from North India,[ 20 ] several genetic studies have been published from India. ( ) A recent study from South India reported 36 different ATP7B mutations, with 13 of them being novel ones.…”
Section: G Enetics Of Wdmentioning
confidence: 99%
“…( ) A recent study from South India reported 36 different ATP7B mutations, with 13 of them being novel ones. [ 19 ] While p.His1069Glu mutation at exon 14 is most frequently reported in European population, p.Arg778Leu missense mutation at exon 8 is most common in Asians. [ 19 21 ] A genetic study involving 43 WD patients from North-West India reported exons 8,12,13,15,16 and 18 as hot spots for mutations.…”
Section: G Enetics Of Wdmentioning
confidence: 99%
See 2 more Smart Citations